ENHANCEMENT OF CANDESARTAN CILEXETIL DISSOLUTION RATE BY USING DIFFERENT METHODS - Raghad, Al-nuss; Hind, El-zein (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â The poor solubility and wettability of candesartan cilexetil (CAN) leads to poor dissolution and hence, low bioavailability after oral administration. The aim of this study was to improve the dissolution rate and hence the bioavailability of CAN by preparing solid dispersions (SD)/inclusion complexes (IC) and liquisolid (LS) systems. SD were prepared using polyethylene glycol (PEG) 6000 (hydrophilic polymer) by melting method in different drugto- carrier ratios (1:2, 1:4 weight ratio), while IC (IC1:1 molar ratio) were made with hydroxypropyl-Î² cyclodextrin (complexing agent) by kneading method. LS systems were prepared using PEG 400 as the nonvolatile solvent, Avicel PH102 as carrier, Aerosil 200 as the coating material. Based on the drug release studies from SDs, SD1:4 was selected to prepare tablets, because it showed an enhanced dissolution profile in comparison with pure drug and SD1:2 according to two-tailed Student’s t-test (p<0.05), in order to compare them with IC1:1 tablets, and LS systems and the marketed product. Fourier transform infrared, and differential scanning calorimetry studies indicated no interaction of the drug with the carriers, and provided valuable insight on the possible reasons for enhanced dissolution profile. Dissolution studies showed that LS systems enhanced dissolution profile of CAN compared with SD (SD1:4) tablets, IC1:1 tablets and the marketed product. The overall rank order given for the various formulations when compared with marketed tablets was: LS tablets > SD1:4 tablets > IC1:1 tablet > marketed tablets. Thus, the SD/IC technique and LS systems can be successfully used for enhancement of the dissolution profile of CAN. Keywords: Candesartan cilexetil, Liquisolid systems, Solid dispirions, Inclusion complexes. Â